Investigation of a Low-power Thruster on Krypton Propellant. (2017) - Saevets, P.A.; Kim, V.P.; Grdlichko, D.P.; Smirnov, P.G.
Abstract: Nowadays, higher requirements are set for modern spacecraft, and, in particular, those related to the cost-efficiency of the mission. To ensure a reasonably long period of active life (approximately 10-15 years), stationary plasma thrusters (SPT) are successfully used in propulsion systems. Xenon is the substantial part of the cost of the propulsion system, which is why this could be significantly reduced, were xenon to be replaced with an alternative propellant. On this basis, and taking into account the perspectives for the creation of multi- satellite orbital constellations and the tendency towards spacecraft miniaturizations, there is a demand for the development of a low-power thruster using an alternative propellant to Xenon. It is assumed that krypton is the most suitable replacement, albeit while using krypton there is a considerable decrease in the SPT thrust parameters. Therefore, it is necessary to perform investigations which reduce the negative consequences related to the use of krypton as a propellant.